Hubungan Berat Badan Lahir Bayi Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Gunungsari Kabupaten Lombok Barat - Albayani, Melati Inayati; Mardani, Raden Ahmad Dedy; Arifin, Zaenal (Jurnal Kesehatan Qamarul Huda, 2020)
Stunting is a chronic malnutrition problem caused by a prolonged lack of nutrition due to feeding that is not in accordance with nutritional needs. The high incidence of stunting and LBW is a problem. The aim of this study was to analyze the relationship between birth weight and the incidence of stunting in children under five at Gunungsari Health Center, West Lombok. This type of research is an analytic survey method through a cross sectional approach with a total sample of 162 people, taken using purposive sampling. The independent variable is birth weight. The dependent variable in this study is stunting. The results showed that there was a relationship between birth weight and the incidence of stunting in children under five at Gunungsari Health Center, West Lombok in 2019, the P value = 0.000 with OR = 4.01 (95% CI: 1.99 - 8.09), which This means that children who have a history of LBW have a 4.01 times greater risk of being very short compared to children born without LBW. Â